“Lumbar swelling: And up into the lungs…” A radiology case report of spinal tuberculosis - Manithodika, Asnath; Vejalla, Jyoshna; Nambiar, Akhil R; Deepa, S (Indian Journal of Case Reports, 2024)
Spinal tuberculosis is one form of extra-pulmonary tuberculosis which usually has delayed presentation with spinal deformities in most cases. The para-spinal soft-tissue involvement can lead to a cold abscess which can present as swellings, mainly in the neck and lumbar regions. Here, a case of a young man is being presented, who had lumbar swelling which on computed tomography evaluation showed para-spinal collection, vertebral lytic foci, and lung parenchymal lesions suggestive of infection.